Guardian of the presidency : the legacy of Richard E. Neustadt - Dickinson, Matthew J.; Neustadt, Elizabeth A. (Brookings Institution Press, 2007)
"Richard Neustadt's former colleagues and students celebrate the rich and diverse contributions he made to political and academic life in the United States and beyond"--Provided by publisher